Occurrence patterns of L. pulmonaria and its host trees (aspen and goat willow), together with 400-year fire history data, Teerisuo-Lososuo, Finland - Fabritius, Henna; Lankia, Heini; Wallenius, Tuomo; Várkonyi, Gergely; Pennanen, Juho; Snäll, Tord (Swedish University of Agricultural Sciences, 2019)
This data archive contains data used in the study by Fabritius et al. (2019): Estimation of metapopulation colonization rates from disturbance history and occurrence pattern data, Ecology. All data have been previously used also in other studies (Gu et al. 2001, Snäll et al. 2005, Lankia et al. 2012, Ronnås et al. 2017).

The data include two-time-point occurrence pattern data of an endangered lichen L. pulmonaria, empirical snapshot data on aspen (P. tremula) and goat willow (S. caprea) counts, and 400-year data of forest fires. All data have been collected in the Teerisuo-Lososuo nature reserve, Kuhmo, Finland (2 086 ha; 63°88'N, 29°18'E) and projected in the Finnish YKJ projection.

Ilkka Hanski initiated the surveys in the late 1990’s and Gergely Várkonyi, Matti Komulainen, Jari Huotari, Pirjo Appelgren and Mikko Heikura assisted with field work.

The data include two-time-point occurrence pattern data of an endangered lichen L. pulmonaria, empirical snapshot data on aspen (P. tremula) and goat willow (S. caprea) counts, and 400-year data of forest fires. All data have been collected in the Teerisuo-Lososuo nature reserve, Kuhmo, Finland (2 086 ha; 63°88'N, 29°18'E) and projected in the Finnish YKJ projection, EPSG:2393.

Materialet innehåller data som användes i studien av Fabritius m. fl. (2019): Estimation of metapopulation colonization rates from disturbance history and occurrence pattern data, tidskrift Ecology. Alla data har tidigare använts även i andra studier (Gu et al 2001, Snäll et al. 2005, Lankia et al., 2012, Ronnås et al., 2017).

Uppgifterna innehåller data på förekomstmönster från två tillfällen för lunglav (Lobaria pulmonaria), förekomstmönster för asp (Populus tremula) och sälg (Salix caprea), samt 400 års data från skogsbränder. Alla uppgifter har samlats in under 1997-2010 i Teerisuo-Lososuo naturreservat, Kuhmo, Finland (2 086 ha, 63 ° 88'N, 29 ° 18'E) och projiceras i Finlands YKJ-projektion.

Ilkka Hanski initierade undersökningarna i slutet av 1990-talet och Gergely Várkonyi, Matti Komulainen, Jari Huotari, Pirjo Appelgren och Mikko Heikura assisterade med fältarbete.

Uppgifterna innehåller data på förekomstmönster från två tillfällen för lunglav (Lobaria pulmonaria), förekomstmönster för asp (Populus tremula) och sälg (Salix caprea), samt 400 års data från skogsbränder. Alla uppgifter har samlats in under 1997-2010 i Teerisuo-Lososuo naturreservat, Kuhmo, Finland (2 086 ha, 63 ° 88'N, 29 ° 18'E) och projiceras i Finlands YKJ-projektion, EPSG:2393.
Förekomstdata på lunglav (Lobaria pulmonaria), på dess värdträd asp (Populus tremula) och sälg (Salix caprea) samt från skogsbränder under en 400-årsperiod, Teerisuo-Lososuo naturreservat, Kuhmo, Finland
Keywords: FIRE MODELS; FIRE HISTORY; FIRE SCAR DATE; land cover; land-cover; forest disturbance; disturbance ecology; disturbance pattern; Bio-geographical regions; Biogeografiska regioner; Habitats and biotopes; Naturtyper och biotoper; occurrence pattern data; utbredningsdata; Salix caprea; Salix caprea; Populus tremula; Populus tremula; Lobaria pulmonaria; Lobaria pulmonaria; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Imagery / Base Maps / Earth Cover; Arealtäckande bilder och bakgrundskartor; Biota; Biologi och ekologi; Environment; Miljö